Large reduction in electrical contact resistance of flexible carbon nanotube/silicone rubber composites by trifluoroacetic acid treatment. (3rd May 2017) - Lee, Sang-Eui; Jee, Sang Soo; Park, Hyokeun; Park, Sung-Hoon; Han, Intaek; Mizusaki, Soichiro
Abstract: We report a large reduction in contact resistance between stretchable carbon nanotube/silicone rubber composites and silver electrodes by a chemical surface treatment, accompanied by an enhancement in the electrical conductivity of the composites. The reactive solvent, trifluoroacetic acid, works for the purpose. In addition, the treatment makes a uniform etching in a micro level with little sacrifice in surface roughness of the nanocomposites. The electrical conductivity of 1.0 wt% nanotube composite was enhanced approximately two-fold and three-fold by ten- and thirty-second treatment, which was induced by the reduction in the contact resistance to one half of an original value. It is meaningful that our finding can be an approach to reduce the nanoparticle loading while keeping electrical conductivity in a high level, which can be crucial for securing flexibility or stretchability in a viewpoint that the elongation is inversely proportional to the conductive particle loading.